2019
DOI: 10.3390/agronomy9070399
|View full text |Cite
|
Sign up to set email alerts
|

Morphological Description and Classification of Wheat Kernels Based on Geometric Models

Abstract: Modern automated and semi-automated methods of shape analysis depart from the coordinates of the points in the outline of a figure and obtain, based on artificial vision algorithms, descriptive parameters (i.e., the length, width, area, and circularity index). These methods omit an important factor: the resemblance of the examined images to a geometric figure. We have described a method based on the comparison of the outline of seed images with geometric figures. The J index is the percentage of similarity bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
39
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(40 citation statements)
references
References 27 publications
1
39
0
Order By: Relevance
“…Previous studies on seed sculpture have shown its usefulness in plant taxonomy, as seen for Asteraceae (Shabestari et al, 2013), Caryophyllaceae , Poaceae (Martín-Gómez, Rewicz, Goriewa-Duba, et al, 2019), Ranunculaceae (Hadidchi et al, 2020;Rewicz et al, 2017), and Orchidaceae (Ortúñez et al, 2006;Rewicz et al, 2016). Our research is the first insight into the seed ultrastructure of five species from the genus Impatiens from Northeast India.…”
Section: Discussionmentioning
confidence: 58%
“…Previous studies on seed sculpture have shown its usefulness in plant taxonomy, as seen for Asteraceae (Shabestari et al, 2013), Caryophyllaceae , Poaceae (Martín-Gómez, Rewicz, Goriewa-Duba, et al, 2019), Ranunculaceae (Hadidchi et al, 2020;Rewicz et al, 2017), and Orchidaceae (Ortúñez et al, 2006;Rewicz et al, 2016). Our research is the first insight into the seed ultrastructure of five species from the genus Impatiens from Northeast India.…”
Section: Discussionmentioning
confidence: 58%
“…The seeds of Ricinus communis L. and Jatropha curcas L. in the Euphorbiaceae and those of cultivars of Triticum sp. in the Poaceae adjust well to ellipses of varied x/y ratio [ 24 , 25 , 26 ]. Oval shaped seeds occur frequently in the Cucurbitaceae, Berberidaceae, Eupteleaceae and Lardizabalaceae [ 27 , 28 ], while the cardioid is more common in Papaveraceae [ 28 ].…”
Section: Seed Morphology In the Vitaceaementioning
confidence: 99%
“…aestivum, cv. Torke or Zebra for example), the latter being more rounded [25,26]. Also, seed shape may vary in plants grown in different geographic regions or climatic conditions, as observed in Olea europaea L. [27], Jatropha curcas L. [28], and Ricinus communis L. [29,30].…”
Section: Variations In Seed Shapementioning
confidence: 99%